The research on optimal parking space choice model in parking lots - Mingkai Chen; Chao Hu; Tianhai Chang (2011 3rd International Conference on Computer Research and Development, 2011)
In order to deal with the parking guidance issue of the parking guidance and information system in the parking lots, the behavior of choosing parking space was analyzed to build the optimal parking space choice model in the parking lots. Based on the specific situation of the parking lots, the habits and preferences of the drivers when parking their cars were all taken into consideration in this model. After summarizing the key factors which may influence drivers' parking space choice, a multiple attribute decision parking model is proposed to help PGIS in the parking lots choose the optimal parking space for drivers. A case is presented to verify the proposed model. The results show that the model can choose the optimal parking space and provide effective guidance for drivers. It can also take the drivers less time to find the parking space and it will take great help to the intelligent management for the parking guidance and information system, too.